Therapeutic Approaches Targeting MYC-Driven Prostate Cancer - Rebello, Richard J. (Genes (Basel), 2017)
The transcript encoding the proto-oncogene MYC is commonly overexpressed in prostate cancer (PC). MYC protein abundance is also increased in the majority of cases of advanced and metastatic castrate-resistant PC (mCRPC). Accordingly, the MYC-directed transcriptional program directly contributes to PC by upregulating the expression of a number of pro-tumorigenic factors involved in cell growth and proliferation. A key cellular process downstream of MYC activity is the regulation of ribosome biogenesis which sustains tumor growth. MYC activity also cooperates with the dysregulation of the phosphoinositol-3-kinase (PI3K)/AKT/mTOR pathway to promote PC cell survival. Recent advances in the understanding of these interactions through the use of animal models have provided significant insight into the therapeutic efficacy of targeting MYC activity by interfering with its transcriptional program, and indirectly by targeting downstream cellular events linked to MYC transformation potential.